DESIGN OF SCHOOL FORMED CLOTHING: FUNCTIONAL AND ESTHETIC ASPECTS - Васильєва, О. С. (Art and Design, 2019)
Investigate the modern tasks of designing school uniforms. Determine the functions and purpose of this product range and identify the features of preferences of modern consumers. Approach was applied, containing an analysis of scientific sources related to the design of school uniforms and children’s clothing, a system-structural and morphological analysis of the object of study. Theoretically investigated and summarized the main aspects related to the design of children’s clothing and school uniforms. It was revealed that school uniforms should be considered as a “uniform” and as an “element of corporate culture”. The importance of socio-aesthetic functions of school uniforms in the formation of the personality of the student, study and discipline. The main components of this clothing as “an element of corporate culture” are identified: the color gamut, the visual symbol (overall costume geometry and proportions), completeness and symbolism. Analysis of the survey results among schoolchildren and their parents showed consumer preferences in the choice of colors: blue, black and gray. The study of the proportions that were used in the development of the range of modern school uniforms for children of primary school groups. On the basis of analytical studies, the main aspects of the socio-cultural and technical components of the design of school uniforms are identified and systematized. The basic proportional systems used in the design of school uniforms for children of the younger school age group are identified. The results an opportunity for a deeper understanding of the components of the design design of school uniforms, and is the possibility of using the results in further research of the design of school uniforms.